Personal and Occupational Risk Factors of Low Back Pain in Hospital Administration Workers - Setyawan, Haris; Lusi Ismayenti; Isna Qadrijati; Seviana Rinawati; Ratna Fajariani; Tutug Bolet Atmojo; Tyas Lilia Wardani; Hengky Ditya Eko Nugroho; Nabylla Sharfina Sekar Nurriwanti; Ayu Prima Kartika (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Around 223.5 million individuals experienced low back pain, and there were 63.7 million years lived with disability. Multiple studies have identified various risk factors that contribute to the development and persistence of LBP in this demographic, including personal and occupational risk factors. This study aims to investigate personal and occupational risk factors causing LBP complaints among administrative workers at the two largest hospitals in Surakarta City, Indonesia. This study was an analytical observational study with a cross-sectional design conducted at RSUNS and RSDM in June-July 2024, using purposive sampling to select 130 respondents. This study used a questionnaire to collect data on personal and work risk factors such as age, education, gender, length of service, medical history, sitting position, chair backrest height, and duration of sitting in the office. The data was processed using the Somers D test to determine the correlation between the independent and dependent variables. This study found that key occupational risk factors, such as sitting position (p = 0.688), height of chair backrest (p = 0.372), and duration of sitting at the office (p = 0.283), showed no significant correlation to low back pain (LBP) among hospital administrative workers. However, over half of the respondents reported experiencing moderate LBP, highlighting it as an occupational health issue. The findings suggest that commonly measured ergonomic indicators alone may not adequately assess LBP risk in this setting. Therefore, hospitals should implement structured active breaks, work mobility/rest periods, and health education about prolonged sitting.